Translation of phrasal verbs into Indonesian - I Dewa Ayu Devi Maharani Santika; I Gusti Vina Widiadnya Putri; Ni Wayan Suastini (English, 2018)
Phrasal verb is the common word form used in colloquial language, for written and spoken. Although this phrasal is formed from a verb, most of the time the meaning will change after transformed into phrasal verb, but sometimes it does not change its meaning and even gives emphasize on the meaning. This fact is very important to determine the selection of their equivalents in doing the translation. This is a qualitative research which used descriptive analysis in analyzing the data. The data were the translations of an English text into Indonesian language conducted by the primary school teachers in some private schools in Denpasar. Questioner was also applied in order to collect more accurate data for supporting the research analysis. In a short way, the results of this research are (1) there were variant words in choosing the equivalents of the phrasal verbs given. (2) Most of the equivalents of the phrasal verbs were pertinent with their based-meaning in the source language. (3) The common strategy used was Translation by a more neutral/less expressive words; where the chosen equivalents have less expressive words than in their language source, but their meanings are close to the meanings in the source language.